Plasma modeling : methods and applications - Colonna, Gianpiero; D'Angola, Antonio (IOP (Series). Release 22., 2022)
Plasma Modeling: Methods and applications presents and discusses the different approaches that can be adopted for plasma modeling, giving details about theoretical and numerical methods.